Peran Audit Siklus Utang dalam Menjaga Akuntabilitas dan Transfaransi Laporan Keuangan - Tia Permatasari; Ahmad Afreza Bahri; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
Financial statements are the main means of accountability for entities to their stakeholders, so that accountability and transparency in their presentation are an integral requirement of good financial governance practices, especially in the management of debt, which has high risk implications. This study aims to analyze the role of debt cycle audits in strengthening accountability and transparency in financial reporting at companies in Indonesia. The research method used is a qualitative approach through a literature study by examining scientific journals, accounting textbooks, and research publications relevant to auditing, the debt cycle, and the quality of financial reports. The results and discussion show that debt cycle audits play an important role in ensuring the fairness of recognition, measurement, and disclosure of liabilities, strengthening internal control systems, and reducing the risk of misstatement and reporting fraud. Audits have also been proven to increase the disclosure of information on liabilities, which has an impact on the trust of investors, creditors, and the public. The conclusion of this study confirms that auditing the debt cycle is a strategic instrument in realizing accountable, transparent, and ethical financial statements.